2022
DOI: 10.1177/17590914221145105
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Characteristics of Microglia Preparations Generated Using Different Human iPSC-Based Differentiation Methods to Model Neurodegenerative Diseases

Abstract: As the resident immune cells of the healthy nervous system, homeostatic microglia can rapidly become activated in response to injury/disease. Dysregulated microglia activation is a hallmark of nervous system disorders including neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) and Alzheimer's disease. The elucidation of the biological and pathological roles of microglia has recently benefitted from the development of microglia-like cells using human induced pluripotent stem cell (iPSC)-bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…While hiPSC-derived microglia have been used to study neurodegenerative disorders [ 82 , 177 , 190 ], few studies to date have harnessed this model for SZ research. A study modelling early-life stress by exposing microglial precursors to glucocorticoids found that an increased type I interferon signalling and cellular senescence in the matured cells [ 211 ].…”
Section: Introductionmentioning
confidence: 99%
“…While hiPSC-derived microglia have been used to study neurodegenerative disorders [ 82 , 177 , 190 ], few studies to date have harnessed this model for SZ research. A study modelling early-life stress by exposing microglial precursors to glucocorticoids found that an increased type I interferon signalling and cellular senescence in the matured cells [ 211 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its inception, the iPSC technology has offered an almost unlimited access to in vitro models of human brain cells that are otherwise difficult to obtain from primary human brain tissue (Takahashi et al, 2007;Yu et al, 2007;Shi et al, 2017;Li et al, 2018;Li and Shi, 2020;Tong et al, 2021). Various protocols to differentiate macrophage-and microglia-like cells (iMGs) from iPSCs have been developed (Abud et al, 2017;Lee et al, 2018;McQuade et al, 2018;Pocock and Piers, 2018;Hasselmann and Blurton-Jones, 2020;Tang et al, 2022;Washer et al, 2022). Notably, iPSC differentiation into iMGs entails mesodermal specification and transition of the differentiating cells through an erythromyeloid-like progenitor, reminiscent of primitive hematopoiesis (Buchrieser et al, 2017;Lee et al, 2018).…”
Section: Human Ipsc-derived Macrophages and Microgliamentioning
confidence: 99%